DEVELOPING PISA-LIKE MATHEMATICS PROBLEMS ON UNCERTAINTY AND DATA USING ASIAN GAMES FOOTBALL CONTEXT - Yansen, Dedi; Putri, Ratu Ilma Indra; Zulkardi, Zulkardi; Fatimah, Siti (Journal on Mathematics Education, 2019)
This study aims to generate the valid and practical PISA-like mathematics problems on uncertainty and data using the football game context of Asian Games. It also aims to see the potential effects of the problems towards the high school students’ mathematical ability. This study used a design research methodology with the type of development study which was divided into two stages, namely preliminary stage and formative evaluation stage. The preliminary stage covered the analysis of research subjects, curriculum analysis, PISA framework and creating a question instrument. The formative evaluation stage included the one to one consisting of three students together with expert review consisting of two validators, small group consisting of six students, and then the field test. This study produced valid and practical PISA-like mathematics problems on uncertainty and data content which have a potential effect on the senior high school students’ mathematical literacy ability. The validity was determined based on the expert review, while the practicality was determined based on one-to-one and small group assessment. The students' mathematical literacy abilities appeared during the research were communication, reasoning and argument, and devising strategies for problem-solving.